Oromandibular Dystonia-Meige's Syndrome: Report of a Rare Case with Review - Siddharth Gupta; Basavaraj T Bhagwati (Wolters Kluwer Medknow Publications, 2010)
Meige's syndrome is a combination of two forma of dystonia; blepharospasm and oromandibular dystonia (OMD). Oromandibular dystonia (OMD) is a form of focal dystonia affecting head and neck region, including the lower face, jaw, tongue and larynx. It may be a factor contributing to muscle stiffness, degenerative changes in temporomandibular joint, mucosal lesions, damage to teeth, and dental prosthesis. We take this opportunity to present a patient with oromandibular dystonia associated with blepharospasm and spasmodic dysphonia.